2023
DOI: 10.7717/peerj.16021
|View full text |Cite
|
Sign up to set email alerts
|

Claw shape variation in oribatid mites of the genera Carabodes and Caleremaeus: exploring the interplay of habitat, ecology and phylogenetics

Michaela Kerschbaumer,
Sylvia Schäffer,
Tobias Pfingstl

Abstract: Background Claws are a commonly observed biological adaptation across a wide range of animal groups. They serve different functions and their link to evolution is challenging to analyze. While there are many studies on the comparative anatomy and morphology of claws in reptiles, birds and several arthropods, knowledge about claws of soil-living oribatid mites, is still limited. Recent research on intertidal oribatid mites has shown that claw shape is strongly correlated with microhabitat and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 42 publications
(63 reference statements)
2
6
0
Order By: Relevance
“…However, we aim to explore this aspect more thoroughly in future studies to make clearer statements about the correlation between claw morphology and substrate. Anyway, an initial study on the claws of terrestrial Caleremaeus and Carabodes could not infer such a direct correlation but concluded that strong habitat specificity may have a considerable impact on claw shape, whereas the nature of this impact remained unsolved 27 . The present study provides further interesting insights but is also unable to infer a clear correlation between substrate and claw shape as shown in intertidal oribatid mites.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we aim to explore this aspect more thoroughly in future studies to make clearer statements about the correlation between claw morphology and substrate. Anyway, an initial study on the claws of terrestrial Caleremaeus and Carabodes could not infer such a direct correlation but concluded that strong habitat specificity may have a considerable impact on claw shape, whereas the nature of this impact remained unsolved 27 . The present study provides further interesting insights but is also unable to infer a clear correlation between substrate and claw shape as shown in intertidal oribatid mites.…”
Section: Discussionmentioning
confidence: 99%
“…less curvature is linked with softer substrates. But if we look at the species with claw curvatures smaller than 90°, which means their claws are strongly curved, only Caleremaeus alpinus is known to predominantly occur in mosses on rocks and thus on hard substrates 27 . All the other species dwell in habitats with softer substrates, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations